Investigating the extent of Information Technology (IT) usage in Malaysian Batik industry / Yap May Lin, Yap Bee Wah and Jasber Kaur Gian Singh - Yap, May Lin; Yap, Bee Wah; Kaur, Jasber Gian Singh (Institute of Research, Development and Commercialization (IRDC), 2006)
In this new information technology era, business enterprises in Malaysia should capitalize on the use of information technology (IT) to gain the competitive advantage and bring their businesses to the global forefront. The recent advancement of information technology enables a community network portal to provide faster and more efficient communication, dissemination of information and business transactionsfor organizations. This paper discusses the extent of IT usage in the Malaysian Batik Industry and then proposes a community net portal (CNP) reference model for the Malaysian batik industry.